Electricity storage based on coupled thermochemical reactions: The Thermochemical Battery. (January 2021) - Lutz, Michael; Schmidt, Matthias; Bürger, Inga; Linder, Marc
Highlights: Innovative principle for electricity storage is assessed A thermochemical battery is analyzed based on fundamental thermodynamics Two coupled thermochemical gas-solid reactions are used as gas pressure reservoirs Principle can be transferred to a variety of gas-solid reaction systems Abstract: Thermochemical reactions are under investigation for a wide variety of applications. However, the system of two coupled gas-solid reactions exchanging both thermal energy and gas solely with each other has not been investigated yet. This approach allows realizing a compact thermochemical unit with two gas reservoirs at different pressure levels at approximately the same temperature. In this work, such a system is fundamentally analyzed and its technical potential as an energy storage component is investigated. While any two thermochemical gas-solid system can be used, this work exemplarily focusses on metal hydrides. Based on a thermodynamic analysis, it can be shown that the system is feasible, as the intrinsic difference in the reaction enthalpies of the metal hydrides can be compensated with heat integration of the compression unit. Following these findings, a thermochemical battery is investigated in more detail including an energetic analysis of efficiencies and potential storage densities. It is deduced that a higher pressure ratio between the hydrides yields in higher storage density but lower efficiency. Co-generation of cooling energy during discharging is feasible. Graphical abstract: Image, graphical abstract